Ambientalização do currículo e sua influência na atuação profissional voltada à sustentabilidade: um estudo de caso em cursos de agronomia em duas universidades paranaenses - Borges , Ceyça Lia Palerosi (2021)
The discussion around Curriculum Greening (CG) in High Education is becoming an urgent theme. In the agronomy science’s courses, which graduates professionals with a direct contact with natural resources, the CG adds to the technical knowledge an apprenticenship and a commitment with environmental issues, contributing to the Rural Sustainable Development. In this context, the aim of this study is to analyse the curriculum differences around the environmental issues presented in the curriculums and the influence of the professional performance of the graduates of two Paraná’s Universities, Universidade Federal da Fronteira Sul (UFFS), campus Laranjeiras do Sul, and UNIOESTE, campus Marechal Cândido Rondon. This is a qualitative research caractherized as an explained case study, whose data collect techniques are: integrative review, documental research and semi structured interview. There were realized 21 interviews with the professors of the 48 selected, with four course’s coordinators (the first and the actual) and with 41 graduates of the last five years. The integrative review demonstrates the absence of research about CG in High Education in agronomy science’s courses in the national and international scenes, suggesting the necessity of more studies that investigate the CG in these courses. In other sciences, the success of the CG is related to the professor experience and formation in the environmental area as well as in educational methods that are better applied in environmental problems. These are observations that the graduates also do. When the 10 caractheristics of Rede ACES to have a CG are analysed, the role of the professor is also indicated. In this way, even in courses with a sustainable enphasis, as UFF’s agronomy course, the professor techniques during the teaching and apprenticenship process are the diferencial to the CG success in the graduate formation. Thus, it is compreensival the resemblance of Rede ACES’s caractheristics presence in the curriculum of both the courses investigated, even though UNIOESTE has less disciplines that discusses the environmental thematic compared to UFFS. Despite the identification of the CG in both courses, the professional area of most of the graduates is the conventional agriculture, directing the logic of these young professionals to the market’s interests, especially productivity. Even facing numerous challenges, 20% and 25% of the UFFS and UNIOESTE graduates, respectivilly, are working with agroecology, signaling a path of change. Therefore, against the scarce job opportunity in agroecology, the universities efforts aiming the CG does not result in effective change if the labor market does not offer enough jobs in the sustainable area. Consequently, the curriculum reform and teacher training need to be accompained by public policies that encourage the market to offer jobs in agroecology, in order to employ graduates that have a greening education and to contribute in the changes of agronomic’s practices and in the sustainability of the rural area, promoting health and quality of life.